PERLINDUNGAN HUKUM DALAM KONTRAK KOMERSIAL ELEKTRONIK: ANALISIS KOMPREHENSIF TANTANGAN, IMPLEMENTASI, DAN KERANGKA REGULASI DALAM TRANSFORMASI EKONOMI DIGITAL INDONESIA: JURNAL_IJOSPL_FINAL_BENAR - Niamualago Laia - Sitepu, Karolina; Laia, Niamualago; Laia, Yurmanius; Ndruru, Hadirin; Gulo, Boby Putra Meiman (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The exponential growth of Indonesia's digital economy has fundamentally transformed the paradigm of commercial transactions, with electronic contracts emerging as the predominant mechanism for conducting business operations across diverse sectors. This comprehensive research examines the multifaceted legal protection framework governing electronic commercial contracts in Indonesia, conducting an in-depth analysis of implementation challenges, regulatory effectiveness, and the adequacy of existing legal mechanisms in addressing the complexities of digital commerce. Employing a rigorous normative legal research methodology, this study systematically examines Law No. 19 of 2016 concerning Electronic Information and Transactions (ITE Law), Government Regulation No. 71 of 2019 on Electronic System and Transaction Implementation, Law No. 27 of 2022 concerning Personal Data Protection, alongside foundational provisions from the Indonesian Civil Code and Law No. 8 of 1999 concerning Consumer Protection. The research reveals that while Indonesia has established a relatively comprehensive legislative framework for electronic contracts, substantial implementation gaps persist, particularly concerning consumer protection enforcement, digital signature authentication infrastructure, cross-border transaction jurisdiction, data privacy safeguards, and dispute resolution mechanisms tailored to digital commerce characteristics. Critical findings indicate that legal certainty in electronic contracts encounters significant obstacles stemming from inadequate digital authentication infrastructure, limited certification authority networks, insufficient public awareness regarding legal rights and obligations in e-commerce transactions, complex jurisdictional challenges in international digital transactions, and the absence of specialized dispute resolution mechanisms designed specifically for electronic commerce disputes. The study identifies critical deficiencies in evidentiary procedures for electronic documents, contractual validity verification processes, consumer protection implementation, and the enforcement of regulatory provisions against non-compliant electronic system operators. This research makes substantial contributions to understanding the legal challenges confronting Indonesia's rapidly evolving digital economy by providing comprehensive analysis of regulatory frameworks, identifying systemic implementation gaps, and offering evidencebased recommendations for strengthening legal protection mechanisms. The findings possess particular relevance for policymakers tasked with regulatory development, legal practitioners navigating electronic contract enforcement, businesses operating in digital marketplaces, academic researchers examining digital commerce law, and consumers seeking to understand their rights in electronic transactions. The research proposes specific recommendations including enhanced inter-agency regulatory coordination, expanded digital authentication infrastructure with subsidized access for small and medium enterprises, comprehensive digital literacy and legal awareness programs, development of specialized online dispute resolution platforms, harmonization with international e-commerce legal standards, and implementation of adaptive regulatory frameworks capable of responding to technological innovation while maintaining adequate protection standards for all stakeholders in Indonesia's digital economy ecosystem.